An introduction to multiagent systems - Wooldridge, Michael J., 1966- (John Wiley & Sons, 2009)
The eagerly anticipated updated resource on one of the most important areas of research and development: multi-agent systems Multi-agent systems allow many intelligent agents to interact with each other, and this field of study has advanced at a rapid pace since the publication of the first edition of this book, which was nearly a decade ago.